How Regional Inequality Affects Fiscal Decentralisation: Accounting for the Autonomy of Subcentral Governments. (February 2014) - Sacchi, Agnese; Salotti, Simone
The aim of this paper is to analyse the influence of regional economic disparities on the fiscal decentralisation processes in twenty-one OECD countries over the period 1981 to 2005. We use novel and robust measures of fiscal decentralisation based on different degrees of autonomy over both expenditures and taxes granted to subcentral governments. Our results show that high regional economic disparities call for lower fiscal decentralisation. This could be interpreted as the outcome of a bargaining process driven by the relative strength and different incentives of rich and poor regions. Moreover, the extent to which responsibility and decision powers are really left to subcentral governments appears to be crucial. Thus, from a positive point of view, equity considerations seem to suggest avoidance of fiscal decentralisation processes in countries with significant regional economic disparities, notwithstanding the well-known efficiency gains.